Multiple micronutrient supplementation improves micronutrient status in primary school children in Hai Phong City, Vietnam: a randomised controlled trial - Ngan T. D. Hoang (Nature Portfolio, 2021)
Abstract We aimed to determine the efficacy of multiple micronutrient supplementation on the biomarkers of iron, zinc, and vitamin A status across anthropometric status categories in Vietnamese school children. In this 22-week randomised controlled trial, 347 undernourished, normal weight, or overweight/obese children aged 6–9 years were allocated to receive every school day a multiple micronutrient supplement (10 mg iron, 10 mg zinc, 400 µg vitamin A) or a placebo. Haematological indices; circulating ferritin, zinc, and retinol (corrected for inflammation); and C-reactive protein were measured at baseline and 22 weeks. At week 22, linear mixed models showed that mean corpuscular volume increased by 0.3 fL, serum ferritin by 9.1 µg/L, plasma zinc by 0.9 µmol/L, and plasma retinol by 15%, and the prevalence of zinc deficiency decreased by 17.3% points in the intervention group compared to placebo. No intervention effects were found for other haematological indices, or the prevalence of anaemia. Multiple micronutrient supplementation for 22 weeks improved the biomarkers of zinc and vitamin A status and some biomarkers of iron status, and reduced the prevalence of zinc deficiency in Vietnamese school children. Trial registration: This trial was registered on 06/09/2016 at www.anzctr.org.au as ACTRN12616001245482.